Environmental Cost Accounting Practices of Restaurants - Jazien C. Abuan; Arly N. Visperas; Alessandra A. Asuncion; Stephen Vincent C. Ayson; Glaiza Mae A. Estioko; Aishle Kyte N. Marzan; Mary Rose B. Mosada (Future Science / FSH-PH Publications, 2026)
Restaurants in Urdaneta City, Pangasinan encounter difficulty in sustainability because of their limited knowledge about and inconsistent application of Environmental Cost Accounting (ECA) methods on some of their main operations like waste disposal, utilities management, and emissions output. Anchored on Sustainable Development Goals (SDGs) 1 (No Poverty), 2 (Zero Hunger), and 3 (Good Health and Well-being), this study looked into the ECA practices of small and medium-sized restaurants situated in selected barangays such as, San Vicente, Nancayasan, Anonas, Cayambanan, Camantiles, and Santo Domingo. Using the descriptive quantitative research, the 30 registered restaurant establishments built the sample size. Restaurant owners or supervisors who have knowledge of daily operations and functional basis with regards to environmental responsibility or practices were the respondents of the study. Collected data were analysed to find out the level of implementation of ECA on waste disposal, utilities management, and emissions output. Statistical analysis was also used to determine the relationship between business profile and ECA factors. Results showed that most of the restaurants have only tried doing business for not more than six years and are generally employing not more than ten workers. ECA practices are generally implemented and among the three indicators, it is utilities management that showed the highest rating, followed by waste disposal and emissions output. There is no correlation between business profile variables and ECA.